Composite electrode material and preparation method thereof

By loading tungsten disulfide on acetylene black and using 4A zeolite as pore-forming agent, porous tungsten disulfide/acetylene black/4A zeolite composite electrode material was prepared, which solved the problems of high hydrogen evolution overpotential, low catalytic activity and poor stability in the production of hydrogen by the existing electrode materials, and achieved high catalytic activity and stability.

CN119663335AInactive Publication Date: 2025-03-21SUZHOU AIBEN TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411459695.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing electrode materials have a large hydrogen evolution overpotential, low catalytic activity and poor stability in hydrogen production, which limits their application in industrial production.

Method used

Porous tungsten disulfide/acetylene black/4A zeolite composite electrode material was prepared by loading tungsten disulfide on acetylene black and using 4A zeolite as the pore-forming agent. This material dissolves 4A zeolites through dilute hydrochloric acid to form a porous structure, which improves the conductivity and exposure of the active site of the material.

Benefits of technology

The composite electrode material exhibits a smaller hydrogen evolution overpotential, higher catalytic activity and higher stability, significantly improving its performance in hydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663335A_ABST
    Figure CN119663335A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, and discloses a composite electrode material and a preparation method thereof, the composite electrode material comprises the following raw materials by weight: 30-40 parts of acetylene black, 36-40 parts of sodium tungstate dihydrate, 40-50 parts of thiourea, 2-3 parts of a cationic detergent, 105-120 parts of concentrated sulfuric acid, 30-40 parts of concentrated nitric acid, 8-10 parts of diluted hydrochloric acid, 45-50 parts of hydrazine monohydrate, 4-5 parts of a pore forming agent, and 80-100 parts of deionized water. Tungsten disulfide is loaded on acetylene black, the advantages of tungsten disulfide and acetylene black are fully played, the conductivity of the composite material is effectively enhanced, the agglomeration degree of WS2 is weakened, meanwhile, 4A zeolite serves as a pore-forming agent, gaps are provided for electron transfer, and the hydrogen evolution performance of the composite electrode material is jointly improved through the synergistic effect of the two aspects; the prepared composite electrode material has relatively small hydrogen evolution overpotential, relatively high catalytic activity and relatively high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a composite electrode material and a preparation method thereof. Background Art

[0002] The current energy shortage problem has become a global problem, and it is of great significance to develop new energy sources with superior performance to cope with the energy crisis. Hydrogen energy is a clean energy with high combustion calorific value and a wide range of sources. As a technology for industrial production of hydrogen, water electrolysis has outstanding advantages such as simple operation, clean and pollution-free, and is considered to be one of the feasible and mature technologies. An efficient and ideal cathode hydrogen evolution electrode material should have characteristics such as small overpotential, large specific surface area, good conductivity, high electrocatalytic activity, and good stability. However, most electrodes cannot be widely used in industrial production due to high energy consumption caused by large hydrogen evolution overpotential and low catalytic activity. Therefore, the preparation of electrode materials with small hydrogen evolution overpotential and high catalytic activity is of vital practical significance both in terms of energy saving and efficiency improvement and in solving the problem of energy shortage in the long run.

[0003] Traditional electrocatalysts based on precious metals, especially platinum, have good catalytic activity, but their high price and rarity limit their practical applications. In recent years, non-platinum hydrogen production electrocatalysts represented by tungsten disulfide (WS2) have attracted widespread attention due to their low cost and high performance. However, studies have found that the electrocatalytic hydrogen production performance of bulk WS2 is very poor. WS2 is a semiconductor, and its weak electron conduction ability also limits its application, so improving its electrical conductivity is also one of the important ways to improve its electrocatalytic performance.

[0004] Chinese patent CN117525351A discloses a Bi / WS2@C composite electrode material and a preparation method thereof. Bi2O3 / WS2 composite material is synthesized by a solvothermal method using Bi2O3 as a template, and 2-methylimidazole is used as a carbon source for coating. The prepared Bi / WS2@C composite electrode material solves the problems of poor rate performance and capacity attenuation in existing battery materials, but still has problems such as large hydrogen evolution overpotential, low catalytic activity, and poor stability. Summary of the invention

[0005] In order to overcome the shortcomings and deficiencies of the prior art, the present invention aims to provide a composite electrode material and a preparation method thereof, wherein the prepared composite electrode material has excellent hydrogen evolution performance, high catalytic activity and high stability.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] A composite electrode material, the raw materials of which are measured by weight and comprise: 30-40 parts of acetylene black, 36-40 parts of sodium tungstate dihydrate, 40-50 parts of thiourea, 2-3 parts of cationic detergent, 105-120 parts of concentrated sulfuric acid, 30-40 parts of concentrated nitric acid, 8-10 parts of dilute hydrochloric acid, 45-50 parts of hydrazine monohydrate, 4-5 parts of pore-forming agent, and 80-100 parts of deionized water.

[0008] Preferably, the cationic detergent is CTAB.

[0009] Preferably, the pore former is 4A zeolite.

[0010] Preferably, the concentration of concentrated sulfuric acid is 18.4 mol / L.

[0011] Preferably, the concentration of concentrated nitric acid is 8 mol / L.

[0012] Preferably, the concentration of the dilute hydrochloric acid is 3 mol / L.

[0013] The method for preparing a composite electrode material comprises the following steps:

[0014] (1) Mix concentrated sulfuric acid and concentrated nitric acid uniformly, add acetylene black, stir and heat, then wash 3-4 times with 10 parts of deionized water, filter and dry to obtain pretreated acetylene black;

[0015] (2) Pretreated acetylene black was dispersed in 50-70 parts of deionized water, ultrasonicated for 2 hours, then sodium tungstate dihydrate and cationic detergent were added, stirred for 30 minutes, then thiourea, hydrazine monohydrate and pore-forming agent were added, ultrasonically dispersed for 1 hour, then stirred, heated for reaction, and after the reaction was completed, the system was naturally cooled to room temperature, filtered, washed with 10 parts of deionized water for 3-4 times, and dried at room temperature to obtain tungsten disulfide / acetylene black / 4A zeolite composite material;

[0016] (3) Adding the tungsten disulfide / acetylene black / 4A zeolite composite material to dilute hydrochloric acid, stirring at room temperature for reaction for 3-5 hours, then filtering, washing with 10 parts of deionized water for 3-4 times, and drying at room temperature to obtain a porous composite electrode material.

[0017] Preferably, the heating temperature in step (1) is 80° C. and the heating time is 5 h.

[0018] Preferably, the drying in step (1) is carried out under vacuum at 80° C. for 24 hours.

[0019] Preferably, the heating temperature in step (2) is 200° C. and the reaction time is 24 h.

[0020] Beneficial effects of the present invention:

[0021] The present invention provides a porous tungsten disulfide / acetylene black composite electrode material and a preparation method thereof. Non-platinum hydrogen production electrocatalysts represented by tungsten disulfide are cheap but have poor electrocatalytic hydrogen production performance and conductivity; acetylene black is a material of carbon black, which has excellent electrochemical properties such as large specific surface area and good conductivity, and is commonly used in the field of electrochemistry. The present invention loads tungsten disulfide on acetylene black, giving full play to the advantages of both, effectively enhancing the conductivity of the composite material and reducing the degree of agglomeration of WS2, while using 4A zeolite as a pore-forming agent to provide gaps for electron transfer. The synergistic effect of the two aspects jointly improves the hydrogen evolution performance of the composite electrode material. After the present invention prepares the tungsten disulfide / acetylene black / 4A zeolite composite material, the 4A zeolite mixed in the composite material is dissolved with dilute hydrochloric acid, so that the composite material presents a porous structure, exposing more active sites, and having a smaller hydrogen evolution overpotential, higher catalytic activity and higher stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 : LSV diagram of each electrode in H2SO4 electrolyte;

[0023] Figure 2 : Comparison of the linear scanning curves of the electrodes of Example 1 and Comparative Example 1 before and after 2000 cycles. DETAILED DESCRIPTION

[0024] The concept and technical effects of the present invention will be clearly and completely described below in conjunction with embodiments to fully understand the purpose, features and effects of the present invention.

[0025] Embodiment 1:

[0026] A composite electrode material, whose raw materials, measured by weight, include: 30 parts of acetylene black, 36 parts of sodium tungstate dihydrate, 40 parts of thiourea, 2 parts of CTAB, 105 parts of concentrated sulfuric acid, 30 parts of concentrated nitric acid, 8 parts of dilute hydrochloric acid, 4 parts of hydrazine monohydrate, 4 parts of 4A zeolite, and 80 parts of deionized water.

[0027] The method for preparing the composite electrode material described in this embodiment comprises the following steps, measured by weight:

[0028] (1) Concentrated sulfuric acid and concentrated nitric acid were mixed evenly, and then acetylene black was added, stirred, heated to 80° C., and reacted for 5 hours, then washed with 10 parts of deionized water for 3 times, filtered, and dried at 80° C. under vacuum conditions for 24 hours to obtain pretreated acetylene black;

[0029] (2) Pretreated acetylene black was dispersed in 50 parts of deionized water, ultrasonicated for 2 hours, then sodium tungstate dihydrate and CTAB were added, stirred for 30 minutes, then thiourea, hydrazine monohydrate and 4A zeolite were added, ultrasonically dispersed for 1 hour, then stirred, heated to 200°C and reacted for 24 hours. After the reaction was completed, the system was naturally cooled to room temperature, filtered, washed 3 times with 10 parts of deionized water, and dried at room temperature to obtain a tungsten disulfide / acetylene black / 4A zeolite composite material;

[0030] (3) The tungsten disulfide / acetylene black / 4A zeolite composite material was added to dilute hydrochloric acid, stirred at room temperature for 3 hours, then filtered, washed three times with 10 parts of deionized water, and dried at room temperature to obtain a porous composite electrode material.

[0031] Embodiment 2:

[0032] A composite electrode material, whose raw materials, measured by weight, include: 35 parts of acetylene black, 38 parts of sodium tungstate dihydrate, 45 parts of thiourea, 2 parts of CTAB, 110 parts of concentrated sulfuric acid, 35 parts of concentrated nitric acid, 9 parts of dilute hydrochloric acid, 45 parts of hydrazine monohydrate, 5 parts of 4A zeolite, and 90 parts of deionized water.

[0033] The method for preparing the composite electrode material described in this embodiment comprises the following steps, measured by weight:

[0034] (1) Concentrated sulfuric acid and concentrated nitric acid were mixed evenly, and then acetylene black was added, stirred, heated to 80° C., and reacted for 5 hours, then washed with 10 parts of deionized water for 3 times, filtered, and dried at 80° C. under vacuum conditions for 24 hours to obtain pretreated acetylene black;

[0035] (2) Pretreated acetylene black was dispersed in 60 parts of deionized water, ultrasonicated for 2 hours, then sodium tungstate dihydrate and CTAB were added, stirred for 30 minutes, then thiourea, hydrazine monohydrate and 4A zeolite were added, ultrasonically dispersed for 1 hour, then stirred, heated to 200°C and reacted for 24 hours. After the reaction was completed, the system was naturally cooled to room temperature, filtered, washed 4 times with 10 parts of deionized water, and dried at room temperature to obtain a tungsten disulfide / acetylene black / 4A zeolite composite material;

[0036] (3) The tungsten disulfide / acetylene black / 4A zeolite composite material was added to dilute hydrochloric acid, stirred at room temperature for 4 hours, then filtered, washed 4 times with 10 parts of deionized water, and dried at room temperature to obtain a porous composite electrode material.

[0037] Embodiment 3:

[0038] A composite electrode material, whose raw materials, measured by weight, include: 40 parts of acetylene black, 40 parts of sodium tungstate dihydrate, 50 parts of thiourea, 3 parts of CTAB, 120 parts of concentrated sulfuric acid, 40 parts of concentrated nitric acid, 10 parts of dilute hydrochloric acid, 50 parts of hydrazine monohydrate, 5 parts of 4A zeolite, and 100 parts of deionized water.

[0039] The method for preparing the composite electrode material described in this embodiment comprises the following steps, measured by weight:

[0040] (1) Concentrated sulfuric acid and concentrated nitric acid were mixed evenly, and then acetylene black was added, stirred, heated to 80° C., and reacted for 5 hours, then washed with 10 parts of deionized water for 4 times, filtered, and dried at 80° C. under vacuum conditions for 24 hours to obtain pretreated acetylene black;

[0041] (2) Pretreated acetylene black was dispersed in 70 parts of deionized water, ultrasonicated for 2 hours, then sodium tungstate dihydrate and CTAB were added, stirred for 30 minutes, then thiourea, hydrazine monohydrate and 4A zeolite were added, ultrasonically dispersed for 1 hour, then stirred, heated to 200°C and reacted for 24 hours. After the reaction was completed, the system was naturally cooled to room temperature, filtered, washed 4 times with 10 parts of deionized water, and dried at room temperature to obtain a tungsten disulfide / acetylene black / 4A zeolite composite material;

[0042] (3) The tungsten disulfide / acetylene black / 4A zeolite composite material was added to dilute hydrochloric acid, stirred at room temperature for 5 hours, then filtered, washed four times with 10 parts of deionized water, and dried at room temperature to obtain a porous composite electrode material.

[0043] Comparative Example 1:

[0044] The difference between this comparative example and Example 1 is that the pretreated acetylene black and 4A zeolite are not added in step (2), and the remaining raw materials and steps are the same as those in Example 1 to prepare tungsten disulfide electrode material.

[0045] Comparative Example 2:

[0046] The difference between this comparative example and Example 1 is that 4A zeolite is not added in step (2), and the remaining raw materials and steps are the same as those in Example 1 to prepare a tungsten disulfide / acetylene black composite electrode material.

[0047] Electrode material performance test:

[0048] 5 mg of the composite electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 were dispersed in 1 mL of H2O: anhydrous ethanol (volume ratio 1:1) and 30 μL of Nafion mixed solution, and ultrasonicated for 30 min to make it evenly dispersed. Then, 5 μL of the suspension was taken with a micro syringe and dropped on the surface of a smooth glassy carbon electrode, and dried naturally to obtain a working electrode of the composite electrode material. A standard hydrogen electrode was used as a reference electrode, a Pt electrode was used as a counter electrode, and together with the working electrode, a three-electrode system was formed to perform a performance test.

[0049] Linear sweep voltammetry (LSV) test: The three-electrode system was placed in a 0.50 mol / L H2SO4 solution for LSV test to characterize the electrocatalytic hydrogen evolution performance of the prepared electrode. The scanning range was -0.6V-0.2V, and the scanning rate was 1mV / s.

[0050] like Figure 1 As shown, under the same hydrogen evolution current density, the tungsten disulfide / acetylene black composite electrode of Comparative Example 2 has a significant positive shift compared with the tungsten disulfide electrode of Comparative Example 1. This is because acetylene black is a good conductive material that can effectively enhance the conductivity of the composite material and greatly enhance the catalytic performance of the hydrogen evolution electrode. The porous tungsten disulfide / acetylene black composite electrode prepared in Example 1 has the smallest hydrogen evolution overpotential and the strongest hydrogen evolution performance. Its potential has the largest positive shift under the same current density. This is because 4A zeolite is co-deposited with acetylene black, making it easier to adsorb on the surface of tungsten disulfide, and 4A zeolite provides a porous structure after acid hydrolysis, providing gaps for electron transfer, and the two work together to improve the hydrogen evolution performance of the composite material.

[0051] Stability test: For the three-electrode system of Example 1 and Comparative Example 1, the initial linear scanning voltammetry curve of the electrode was measured first, then the cyclic voltammetry was scanned for 2000 cycles, and the linear scanning voltammetry curve was measured again, which was the polarization curve after 2000 cycles, to compare the extent of current density reduction at the same potential.

[0052] like Figure 2 As shown, after 2000 cycles of cyclic voltammetry, the polarization curve of Example 1 changes little compared to the initial curve. This is because the addition of acetylene black weakens the degree of agglomeration of WS2, and at the same time, 4A zeolite makes the composite material present a porous structure, exposing more active sites, so that the composite material has higher stability.

[0053] The above embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work shall all fall within the scope of protection of the present invention.

Claims

1. A composite electrode material, characterized in that: The raw materials thereof are calculated by weight and comprise: 30-40 parts of acetylene black, 36-40 parts of sodium tungstate dihydrate, 40-50 parts of thiourea, 2-3 parts of cationic detergent, 105-120 parts of concentrated sulfuric acid, 30-40 parts of concentrated nitric acid, 8-10 parts of dilute hydrochloric acid, 45-50 parts of hydrazine monohydrate, 4-5 parts of pore-forming agent and 80-100 parts of deionized water.

2. A composite electrode material according to claim 1, characterized in that: The cationic detergent is CTAB.

3. A composite electrode material according to claim 1, characterized in that: The pore former is 4A zeolite.

4. A composite electrode material according to claim 1, characterized in that: The concentration of the concentrated sulfuric acid is 18.4 mol / L.

5. A composite electrode material according to claim 1, characterized in that: The concentration of the concentrated nitric acid is 8 mol / L.

6. A composite electrode material according to claim 1, characterized in that: The concentration of the dilute hydrochloric acid is 3 mol / L.

7. A method for preparing a composite electrode material according to claims 1-6, characterized in that: The preparation method comprises the following steps: (1) Mix concentrated sulfuric acid and concentrated nitric acid uniformly, add acetylene black, stir and heat, then wash 3-4 times with 10 parts of deionized water, filter and dry to obtain pretreated acetylene black; (2) Pretreated acetylene black was dispersed in 50-70 parts of deionized water, ultrasonicated for 2 hours, then sodium tungstate dihydrate and cationic detergent were added, stirred for 30 minutes, then thiourea, hydrazine monohydrate and pore-forming agent were added, ultrasonically dispersed for 1 hour, then stirred, heated for reaction, and after the reaction was completed, the system was naturally cooled to room temperature, filtered, washed with 10 parts of deionized water for 3-4 times, and dried at room temperature to obtain tungsten disulfide / acetylene black / 4A zeolite composite material; (3) Adding the tungsten disulfide / acetylene black / 4A zeolite composite material to dilute hydrochloric acid, stirring at room temperature for reaction for 3-5 hours, then filtering, washing with 10 parts of deionized water for 3-4 times, and drying at room temperature to obtain a porous composite electrode material.

8. The method for preparing a composite electrode material according to claim 7, characterized in that: The heating temperature in step (1) is 80° C. and the heating time is 5 h.

9. The method for preparing a composite electrode material according to claim 7, characterized in that: The drying in step (1) is carried out at 80° C. under vacuum conditions for 24 hours.

10. The method for preparing a composite electrode material according to claim 7, characterized in that: The heating temperature in step (2) is 200° C. and the reaction time is 24 h.

Citation Information

Patent Citations

  • Tungsten disulfide / graphene nanobelt composite material and preparation method thereof

    CN105280900A

  • Iron-doped tungsten disulfide / graphene oxide composite electrode material and preparation method and application thereof

    CN115732654A